A Screen for Swainsonine in Select North American Astragalus Species. Issue 4 (23rd March 2017) - Cook, Daniel; Gardner, Dale R.; Pfister, James A.; Lee, Stephen T.; Welch, Kevin D.; Welsh, Stanley L.
Abstract : Swainsonine is found in several plant species worldwide, and causes severe toxicosis in livestock grazing these plants, leading to a chronic condition characterized by weight loss, altered behavior, depression, decreased libido, infertility, and death. Swainsonine has been detected in 13 North American Astragalus species of which eight belong to taxa in four taxonomic sections, the Densifolii, Diphysi, Inflati, and Trichopodi . These sections belong to two larger groups representing several morphologically related species, the Pacific Piptolobi and the small‐flowered Piptolobi. The objective of this study was to screen the other 31 species for swainsonine in sections Densifolii, Diphysi, Inflati, and Trichopodi previously not known to contain swainsonine. Furthermore, to broaden the scope further, 21 species within the 8 sections of the Pacific Piptolobi and the small flowered Piptolobi were screened for swainsonine. Swainsonine was detected for the first time in 36 Astragalus taxa representing 29 species using liquid and gas chromatography coupled with mass spectrometry. Several taxonomic sections were highly enriched in species that contain swainsonine while others were not. A systematic examination for swainsonine in these species will provide important information on the toxic risk of these species and may be a valuable reference for diagnosticians and land managers. Abstract :